High efficiency electrochemical reduction of CO2 beyond the two-electron transfer pathway on grain boundary rich ultra-small SnO2 nanoparticles. Issue 22 (21st May 2018) - Liang, Chenglu; Kim, Byoungsu; Yang, Shize; Yang Liu,; Francisco Woellner, Cristiano; Li, Zhengyuan; Vajtai, Robert; Yang, Wei; Wu, Jingjie; Kenis, Paul J. A.; Ajayan, Pulickel M.
Abstract : Grain boundary rich ultra-small SnO2 nanoparticles exhibited high total FEs towards electrochemical reduction of CO2 with products beyond CO and HCOO − . Abstract : Well crystallized and interconnected SnO2 nanoparticles (<5 nm) were synthesized via oxidation of exfoliated SnS2 sheets. The SnO2 nanoparticles exhibit a high total faradaic efficiency (FE) of 97% towards electrochemical reduction of CO2 at −0.95 V vs. the reversible hydrogen electrode (RHE). The main product ratio of CO/HCOO − which intrinsically correlates to the surface SnO x /Sn ratio variation varies with the applied potential. Beyond CO and HCOO − products formed via the two-electron transfer pathway, hydrocarbons and oxygenates are produced. The formation of hydrocarbon (CH4 ) versus oxygenate (C2 H5 OH) depends on the choice of electrolyte (KOH vs. KHCO3 ), both of which can reach a maximal faradaic efficiency of 10%. The distinctive grain boundary and exposed corner/step sites in the interconnected SnO2 nanoparticles contribute to the high FE of CO2 reduction and unique selectivity.